The macroeconomic effects of fiscal consolidation in dynamic general equilibrium - Tim Schwarzmüller; Maik H. Wolters (Kiel Institute for the World Economy (IfW), 2014)
We provide a systematic analysis of fiscal consolidation in a medium-scale dynamic general equilibrium model. Our results show that the choice of the consolidation instrument is very important, not only with respect to the short- and long-run output effects of the different consolidation strategies, but also regarding the welfare effects and the distributional consequences. Moreover, we show that these aspects become even more important if fiscal consolidation has to be conducted at a binding zero lower bound on nominal interest rates because in this case the negative short-run output costs increase. Our comprehensive analysis of the transmission channels of various fiscal consolidation measures shows that in particular the presence of credit-constrained households who cannot smooth consumption has a large impact on the overall output and welfare effects of fiscal consolidation. Further, it turns out to be important whether a fiscal instrument directly affects private production factors negatively as it is the case for consolidation via government investment and taxes on labor and capital. In these cases the short-run output contraction is large and persistent because either the private or the public capital stock decreases. By contrast, for a consolidation via government consumption, transfers or the consumption tax rate, output recovers much faster.
Keywords: E32; E62; E63; H61; H62; H63; 330; fiscal consolidation; government debt; distortionary taxes; zero lower bound; welfare; monetary-fiscal policy interaction